Chitosan‐based nanoscale systems for doxorubicin delivery: Exploring biomedical application in cancer therapy. Issue 1 (13th September 2022) - Ashrafizadeh, Milad; Hushmandi, Kiavash; Mirzaei, Sepideh; Bokaie, Saied; Bigham, Ashkan; Makvandi, Pooyan; Rabiee, Navid; Thakur, Vijay Kumar; Kumar, Alan Prem; Sharifi, Esmaeel; Varma, Rajender S.; Aref, Amir Reza; et al.
Abstract: Green chemistry has been a growing multidisciplinary field in recent years showing great promise in biomedical applications, especially for cancer therapy. Chitosan (CS) is an abundant biopolymer derived from chitin and is present in insects and fungi. This polysaccharide has favorable characteristics, including biocompatibility, biodegradability, and ease of modification by enzymes and chemicals. CS‐based nanoparticles (CS‐NPs) have shown potential in the treatment of cancer and other diseases, affording targeted delivery and overcoming drug resistance. The current review emphasizes on the application of CS‐NPs for the delivery of a chemotherapeutic agent, doxorubicin (DOX), in cancer therapy as they promote internalization of DOX in cancer cells and prevent the activity of P‐glycoprotein (P‐gp) to reverse drug resistance. These nanoarchitectures can provide co‐delivery of DOX with antitumor agents such as curcumin and cisplatin to induce synergistic cancer therapy. Furthermore, co‐loading of DOX with siRNA, shRNA, and miRNA can suppress tumor progression and provide chemosensitivity. Various nanostructures, including lipid‐, carbon‐, polymeric‐ and metal‐based nanoparticles, are modifiable with CS for DOX delivery, while functionalization of CS‐NPs with ligands such as hyaluronic acid promotes selectivity toward tumor cells and prevents DOX resistance. The CS‐NPs demonstrate high encapsulation efficiency and due to protonation of amine groups of CS, pH‐sensitive release of DOX can occur. Furthermore, redox‐ and light‐responsive CS‐NPs have been prepared for DOX delivery in cancer treatment. Leveraging these characteristics and in view of the biocompatibility of CS‐NPs, we expect to soon see significant progress towards clinical translation.